The Qur’anic Logic in al-Ghazali’s Book al-Qisṭās al-Mustaqīm - Nur, Muhammad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
Throughout the history of Islam, the notion of logic has been controversial. Not only have many muslims prohibited the use of logic, but also the term manṭiq, or the Arab-Islamic translation of ‘logic’, is often underestimated as a mere copy of the Greek logic. This article wants to examine the conception of Qur’anic logic according to al-Ghazali’s book al-Qisṭās al-Mustaqīm. This investigation is imperative especially because we need to establish a clearer conception of logic in Islamic knowledge, in order to help us better understand the link between philosophy and Islam, as well as the rationality of the Qur’an. The main question of this paper is the following: “How is the form of logic that is used by the Qur’an in its argumentation, as explained in al-Ghazali’s book al-Qisṭās al-Mustaqīm?”. This paper finds out that the Qur’an has its own principles of reasoning. It is not only the source of knowledge but also the parameter of human’s knowledge. This parameter, which includes ta’addul (equilibrium), talazum (equivalence), and ta’anud (contradiction), should be used as the basis upon which the plausibility of human’s argumentation and ways of thinking is structured. Al-Ghazali’s conception of the Qur’anic logic is directed to argue against members of the Ta'limiyah school, who refused the use of logic.